Improving the competitiveness of meat processing enterprises in the market of the food industry - Турганбекова, Б. (Journal of Economic Research & Business Administration, 2015)
This article discusses the problem of improving the competitiveness of the food industry, provides the basic direction of improving the competitiveness of the meat industry.